2018
DOI: 10.1158/1940-6207.capr-17-0283
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, Inflammation, and Breast Cancer Pathogenesis in Asian Women

Abstract: Obesity is associated with white adipose tissue (WAT) inflammation in the breast, elevated levels of the estrogen biosynthetic enzyme, aromatase, and systemic changes that predispose to breast cancer development. We examined whether WAT inflammation and its associated systemic effects correlate with body fat levels in an Asian population where body mass index (BMI) is not an accurate assessment of obesity and cancer risk. We also investigated whether biologic differences could account for the greater proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 49 publications
6
36
2
1
Order By: Relevance
“…Lyengar et al recently reported the very interesting findings that menopausal Taiwanese women had pathologically enlarged adipocytes in breast tissue, meaning that more inflammation was involved, despite having a lower BMI than Caucasian women in the United States (22). Our data showed lean patients to more frequently have high-density breast tissue, reflecting lower adipose tissue contents.…”
Section: Discussionsupporting
confidence: 49%
“…Lyengar et al recently reported the very interesting findings that menopausal Taiwanese women had pathologically enlarged adipocytes in breast tissue, meaning that more inflammation was involved, despite having a lower BMI than Caucasian women in the United States (22). Our data showed lean patients to more frequently have high-density breast tissue, reflecting lower adipose tissue contents.…”
Section: Discussionsupporting
confidence: 49%
“…New research is forcing consideration of the disturbing possibility that “obesity‐associated” breast cancer is rising worldwide in women who are not apparently obese. Within the last year, work has shown that certain lean women show elevated biomarkers of inflammation both systemically and locally in breast adipose tissue, which associate with increased aromatase and breast cancer risk . These insights provoke a radical hypothesis: obesity per se is less important for cancer risk than metabolic inflammation , which need not accompany expanded fat depots or elevated body mass at all.…”
Section: Metabolic Inflammation and Breast Cancer Without Obesitymentioning
confidence: 99%
“…There are a variety of inflammatory biomarkers, which may be involved in carcinogenesis [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. One of the major pro-inflammatory cytokines produced by cells in inflamed tissue is Interleukin-6 (IL-6) [ 7 , 8 , 9 , 10 ]. IL-6 has an important role in chronic inflammatory diseases and may play a role in cancer development [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the major pro-inflammatory cytokines produced by cells in inflamed tissue is Interleukin-6 (IL-6) [ 7 , 8 , 9 , 10 ]. IL-6 has an important role in chronic inflammatory diseases and may play a role in cancer development [ 7 , 8 , 9 , 10 ]. However, the current evidence of the link between the IL-6 and BC risk is insufficient [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation